219k views
0 votes
If M = 5x² + 7x - 4 and N = -3x² - 4x + 5, then M - N equals А 2x² + 3x + 1 B 2x² + 11x - 9 C 8x² + 3x + 1 D 8x² + 11x - 9

1 Answer

6 votes

Answer:

D. 8x² + 11x - 9​

Step-by-step explanation:

Given M and N defined as follows:


\begin{gathered} M=5x^2+7x-4 \\ N=-3x^2-4x+5 \end{gathered}

Then:


\begin{gathered} M-N=(5x^2+7x-4)-(-3x^2-4x+5) \\ =5x^2+7x-4+3x^2+4x-5 \\ =5x^2+3x^2+7x+4x-4-5 \\ =8x^2+11x-9 \end{gathered}

The correct choice is D.

User Altumano
by
5.1k points